Prospek Madrasah Swasta â€œAnalisis Peran dan Fungsi Yayasan Pendidikanâ€ - Imran Siregar (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2020)
AbstractThis paper is based on research results that describe the role and function of foundations in fostering madrasas. His findings indicate that the weakening of the role and function of foundations in fostering madrasas, especially in their control functions, results in the existence of madrasas that are unable to compete with educational institutions at the same level as their surroundings. The transfer of control functions by the foundation to a madrasah head indicates that the management process has not been fully developed as a collaborative process between the foundation, the head, and the madrasah committee. The government itself has only played a role at the level of administrative guidance for madrasah institutions and has not yet touched on the aspect of foundations as the owner of madrasah institutions. Therefore, steps are needed to increase the role of foundations in fostering madrasas through strengthening institutional management, strengthening human resources for teaching and education personnel as well as adequate infrastructure to drive the pace of madrasah institutional organization. Supported and strengthened by refreshing mutual agreement in carrying out the vision and mission of madrasah management to achieve shared goals. The knot point, among others, lies in the leadership of the foundation and the head of the madrasa which is strengthened by empowerment support by the government.AbstrakTulisan ini bersumber dari hasil penelitian yang menggambarkan peran dan fungsi yayasan dalam membina madrasah. Temuannya menunjukkan bahwa dengan melemahnya peran dan fungsi yayasan dalam membina madrasah, khususnya pada fungsi pengendalian, berakibat pada eksistensi madrasah yang tidak mampu berkompetisi dengan lembaga pendidikan setingkat di sekitarnya. Penyerahan fungsi pengendalian oleh yayasan pada seorang kepala madrasah, mengindikasikan bahwa proses manajemen belum sepenuhnya dibangun sebagai suatu proses kerjasama antara yayasan, kepala dan komite madrasah. Pihak pemerintah sendiri baru berperan pada tataran pembinaan administratif kelembagaan madrasah dan belum menyentuh pada aspek yayasan sebagai pemilik kelembagaan madrasah. Oleh karena itu diperlukan langkah peningkatan peran yayasan dalam membina madrasah melalui penguatan manajemen kelembagaan, penguatan SDM tenaga pendidik dan tenaga kependidikan serta sarana prasarana yang memadai untuk menggerakkan lajunya organisasi kelembagaan madrasah. Didukung dan diperkuat dengan penyegaran kembali kesepakatan bersama dalam mengemban visi misi pengelolaan madrasah untuk mencapai tujuan bersama yang dinginkan. Titik simpulnya antara lain ada pada kepemimpinan yayasan dan kepala madrasah yang diperkuat dengan dukungan pemberdayaan oleh pemerintah.